Modelling of cell killing due to sparsely ionizing radiation in normoxic and hypoxic conditions and an extension to high LET radiation - Mairani, Andrea; Böhlen, Till T.; Dokić, Ivana; Cabal, Gonzalo; Brons, Stephan; Haberer, Thomas (International journal of radiation biology, 2013)
Purpose: An approach for describing cell killing with sparsely ionizing radiation in normoxic and hypoxic conditions based on the initial number of randomly distributed DNA double-strand breaks (DSB) is proposed. An extension of the model to high linear energy transfer (LET) radiation is also presented.Materials and methods: The model is based on the probabilities that a given DNA giant loop has one DSB or at least two DSB. A linear combination of these two classes of damage gives the mean number of lethal lesions. When coupled with a proper modelling of the spatial distribution of DSB from ion tracks, the formalism can be used to predict cell response to high LET radiation in aerobic conditions.Results: Survival data for sparsely ionizing radiation of cell lines in normoxic/hypoxic conditions were satisfactorily fitted with the proposed parametrization. It is shown that for dose ranges up to about 10 Gy, the model describes tested experimental survival data as good as the linear-quadratic model does. The high LET extension yields a reasonable agreement with data in aerobic conditions.Conclusions: A new survival model has been introduced that is able to describe the most relevant features of cellular dose-response postulating two damage classes.